The effect of news frames and political speech sources on political attitudes: the moderating role of values - Waheed, Moniza; Schuck, Andreas; Neijens, Peter; Vreese, Claes de (Walter de Gruyter, 2015)
This study investigated the extent to which values play a role in affecting citizens’ political attitudes when exposed to different media news frames and political speech sources. To test this, we designed a survey experiment which used news coverage of a political speech concerning the cultural practices of immigrants (N = 337). We manipulated the manner of how the news was framed (episodic vs. thematic) and the source of the speech (domestic vs. foreign politician). Our main finding shows that citizens who scored high on ‘universalism’ were more affected by a foreign source in an episodic news frame, compared to those scoring low on ‘universalism’ in a thematic news frame. On the other hand, in a thematic news frame, the difference between citizens scoring high and low on ‘universalism’ was found for the domestic source. This suggests that values are a fundamental moderator of media effects in determining citizens’ political attitudes.